The site selection of heat islands and its adaptation to satellite imagery based on the TOPSIS model in Mashhad - Mokhtar Karami,; Rahman Zandi,; jalal taheri (تحقیقات کاربردی علوم جغرافیایی)
In recent years with the development of cities coatings of the Earth's has changed surface.  These changes have caused some urban areas to have a few degrees higher than the surrounding temperature. This phenomenon is known as thermal islands. Mashhad is one of the major metropolises in Iran with the problem of thermal islands. Various parameters affect the formation of thermal islands in this city that should be considered. In this study TM, ETM+ and OLI images were used to obtain surface temperature over the period 1987-2016. The study of temporal variations in surface temperature showed that in the studied period, thermal islands were transferred from outside the city to the city. The model for describing the temperature of the surface of the earth has changed and has diminished from the temperature of the city's moderate and cool temperatures, and in contrast, the amount of high temperatures (thermal islands) has increased significantly. The TOPSIS method was also used to obtain the thermal forming factors. 13 natural and human factors affecting the formation of thermal islands were identified. Each expert opinion factor was used to determine the degree of importance. According to experts, the distance from the sanctuary with a weight of %234 and traffic of %155 is the most important and the height with a weight of %022 is least important in the formation of thermal islands. The final results obtained from this model showed that the factors affecting the formation of thermal islands are well recognized and the temperature decreases with these factors.